The Study About Management of Counseling and Guidance Program in Vocational School, Banjarmasin, Indonesia - Jarkawi, Jarkawi; Anwar, Kasypul; Fauzi, Zainal; Madiah, Husnul (International Research-Based Education Journal, 2019)
The counseling and guidance program management as an integral part of education services in school requires the executors to continue in order to improve and develop the service quality. The counseling and guidance have a role to help the learners to be independent, to grow, and to be able to solve their own problems. The implementation of counseling and guidance always undergoes of perfecting. It happens because the problems faced by students always change and get dynamics. The form of activities to do include the socialization of the program to new students, the delivering of materials and services both individual and group, handling students with problems, whether relating to academic problems, personal aspects or violations. While the supervision process includes (a) recording (administration/documentation), (b) evaluation (measurement and assessment of results and work processes and organizational performance), and (c) taking improvement and development step.Keywords: Program Management, Planning, Organization, Implementation, and Controlling